Identification and Strategies For Strengthening The Planning Capacity of Prabumulih City Potential Tourism Area - Novita Wulandari; Akhmad Muftizar; Bachtari Alam Hidayat; Lies Nur Intan (Dinasti International Journal of Education Management And Social Science, 2024)
Inappropriate planning and not in accordance with the potential, the existing conditions will greatly affect the sustainability of a program, activity or development. This study aims to: (1) identify potential tourist areas that can be developed immediately in the short term, and (2) prepare a strategy for strengthening planning capacity oriented to "generate income". The research uses survey methods, the results of the study: there are 3 potential tourist areas in Prabumulih City including: (1) Edagi Park (EduAgroEkologi) West Gunung Ibul Village, (2) Wonosari Park and Garbage Bank Prabumulih City, Wonosari Village, (3) Pineapple Gardens, Patih Galung Village. This is because, the three tours have "champions", as the spirit of innovation, and Human Resources (HR) aware of tourism supported by a sense of belonging to the cleanliness of the surrounding environment. Furthermore, it is necessary to have (1) independent institutional management that manages potential tourist areas, supported by digital promotions, (2) completes the availability of supporting infrastructure in the form of derivative products from the Women Farmers (KWT) group according to their potential, for example: (a) Herbal Products/Jamu, vegetable chips and fish chips in West Gunung Ibul Village, (b) Herbal processed products, handcraft from plastic, pineapple processed products in Wonosari Village, (c) pineapple fiber processed products in the form of yarn, and various clothes, bags, wallets from jumputan cloth, pineapple processed products in the form of jam, sponge cake, lunkhead, chips.